Analisis Perbedaan Kecepatan Waktu Penyediaan Dokumen Rekam Medis Pasien Lama Rawat Jalan Pada Sistem Penjajaran Terminal Digit Filing Dan Straight Numerical Filing - Wulandari, Ayu Fitri; , Sri Sugiarsih, SKM., M.Kes; , Yuli Kusumawati, SKM, M.Kes (Epid) (2016)
Filing system document of medical record is system of using to arrange bundle of medical record in share of filing. Filing sytem is important because if bundle of medical record just only be entried in shares so it will be exited big difficultly al present time will seek again. Intention of the research is to analyse different of time rapidity of supplying document of medical record of manner take care on filing system of terminal digit filing and straight numerical filing. Type of research is analitic observational with approachment cross sectional. Population of research is old patient of manner take care in Regional Public Hospital Sukoharjo Regency and in Regional Public Hospital dr. Soeratno Gemolong. The sample of research is 95 document of medical record in Regional Public Hospital Sukoharjo Regency and 95 document of medical record in Regional Public Hospital dr. Soeratno is taken with technic of sistematic random sampling. Data of research is supplying time of document of medical record of old patientof manner in Sukoharjo Regional Public and old patient of manner take care in Regional Public Hospital dr. Soeratno Gemolong. Analysis of research uses experiment of Independent Sample t-test. The experiment of statistic uses aid of SPSS program. The result of research indictes existence different of supplying time rapidly of document of medical record of manner take care on system juxtaposition of terminal digit filing and straight numerical filing (P-Value = 0,043)